Pengaruh Kecerdasan Emosional Dan Kecerdasan Spiritual Terhadap Kinerja Pegawai Pada Kantor RSUD Haji Provinsi Sulawesi Selatan - Hardiani, Hardiani; Heslina, Heslina; inzani, nurhawania (Jurnal Ilmiah Bongaya, 2022)
ABTRACT The exhibition of representatives who have insight that isn't just on scholarly knowledge, but at the same time is upheld by Enthusiastic Insight and Otherworldly Insight. The impact of passionate knowledge and profound insight on worker execution is significant, on the grounds that it is one of the determinants of representative execution and authoritative achievement and is the way to advance in the present and what's to come. Regarding that, the foundation of the issue brought up in this examination is the means by which the reactions of workers at the Haji Medical clinic Office of South Sulawesi Area impact passionate insight and otherworldly knowledge on representative execution. This investigation means to inspect and examine the impact of passionate insight on worker execution, the impact of otherworldly knowledge on representative execution and the impact of synchronous use of enthusiastic knowledge and profound insight on worker execution. Gathering information utilizing essential information acquired from workers at the Haji Clinic Office of South Sulawesi Region which were then utilized as respondents utilizing the slovin equation subsequent to doing the computations with the goal that the analysts changed upwards of 82 respondents. The aftereffects of the essential information gathered through the dispersion of the poll have been tried with old style presumption tests as ordinariness suppositions, multicollinearity suspicions and heteroscedasticity suppositions. The information examination strategy utilized unmistakable factual investigation procedures and inferential measurable examination. The outcomes showed that either somewhat or at the same time the use of passionate knowledge and profound insight had a positive and huge impact on worker execution so that all proposed speculations were acknowledged. The size of the impact can be seen from the worth of Changed R square where the changed R square worth is 0.484, which implies that 48.4% of representative execution factors are affected by passionate insight and otherworldly knowledge factors and the excess 51.6% is affected by factors not analyzed in research this time. ABTRACT The exhibition of representatives who have insight that isn't just on scholarly knowledge, but at the same time is upheld by Enthusiastic Insight and Otherworldly Insight. The impact of passionate knowledge and profound insight on worker execution is significant, on the grounds that it is one of the determinants of representative execution and authoritative achievement and is the way to advance in the present and what's to come. Regarding that, the foundation of the issue brought up in this examination is the means by which the reactions of workers at the Haji Medical clinic Office of South Sulawesi Area impact passionate insight and otherworldly knowledge on representative execution. This investigation means to inspect and examine the impact of passionate insight on worker execution, the impact of otherworldly knowledge on representative execution and the impact of synchronous use of enthusiastic knowledge and profound insight on worker execution. Gathering information utilizing essential information acquired from workers at the Haji Clinic Office of South Sulawesi Region which were then utilized as respondents utilizing the slovin equation subsequent to doing the computations with the goal that the analysts changed upwards of 82 respondents. The aftereffects of the essential information gathered through the dispersion of the poll have been tried with old style presumption tests as ordinariness suppositions, multicollinearity suspicions and heteroscedasticity suppositions. The information examination strategy utilized unmistakable factual investigation procedures and inferential measurable examination. The outcomes showed that either somewhat or at the same time the use of passionate knowledge and profound insight had a positive and huge impact on worker execution so that all proposed speculations were acknowledged. The size of the impact can be seen from the worth of Changed R square where the changed R square worth is 0.484, which implies that 48.4% of representative execution factors are affected by passionate insight and otherworldly knowledge factors and the excess 51.6% is affected by factors not analyzed in research this time.